Peningkatan Karakter Religius Peserta Didik Melalui Pembiasaan Membaca Asma’ul Husna Di SMPN 1 Ngoro Jombang - Nurul Lailiyah; Rofiqotul Hasanah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2020)
This study is intended to describe the teacher role in improving students’ religious character through the reading habit of Asmaul Husna at SMPN 1 Ngoro Jombang, 2. Describing students’ religious character of SMPN 1 Ngoro Jombang. This research uses qualitative approach. The data collection is done through interviews, observation and documentation. The data then analyzed by reduction, display and verification data. The results show that: 1. the teachers’ role in implementing students’ religious character education through Asmaul Husna reading habit at SMPN 1 Ngoro Jombang, are teachers as: role model, motivator, dynamic, evaluator. 2. The religious character of students at SMPN 1 Ngoro Jombang: a. Character values formed in SMPN 1 Ngoro Jombang: 1). Religious 2). Discipline 3). Responsibility 4). Tolerance 5). Nobel character 6). Diligent 7). Independent. b. The implementation of the Asmaul Husna reading habit by using such methods as: 1). Getting used to: a).hands shaking with the teacher b) lining up in front of the classroom c). Praying before the activity started. 2) Discipline 3) modelling.